TERT gene: its function and dysregulation in cancer. Issue 4 (29th January 2019) - Colebatch, Andrew J; Dobrovic, Alexander; Cooper, Wendy A
Abstract : In this review, we summarise the function and structure of telomerase reverse transcriptase ( TERT ) in humans, including its regulation. The dysregulation of telomerase through TERT promoter mutations across a range of cancers is discussed. The molecular mechanism activated by TERT promoter mutations is outlined. Finally, the timing of TERT promoter mutations during carcinogenesis is reviewed in the context of their potential utility as clinical biomarkers of malignant transformation.